Implementasi Model Cooperative Learning Tipe Jigsaw untuk Meningkatkan Keaktifan Siswa Kelas V dalam Pembelajaran di SDN Keleyan 2 - Nurul Afiyah; Jihan Okta Fayosha; Silvia Agustina; Agung Setyawan; Muhammad Farhan (Journal of Action Research in Education, 2026)
This classroom action research was carried out in Grade V of SDN Keleyan 2 to improve students' active participation in learning through the application of the Jigsaw type Cooperative Learning model. The study was based on the problem of low student involvement during classroom activities, shown by limited interaction in discussions, low confidence in expressing ideas, and minimal participation in responding to the teacher's questions. This research used a classroom action research design conducted in two cycles. Each cycle included planning, action implementation, observation, and reflection. The participants were 25 fifth-grade students of SDN Keleyan 2, consisting of 11 boys and 14 girls. Data were collected through observation, documentation, and student activeness assessment sheets. The findings indicate that the Jigsaw type Cooperative Learning model improved student activeness. The improvement was reflected in more students taking part in group discussions, increased confidence in sharing ideas, and greater involvement in presenting discussion results. Learning through the Jigsaw model gave students opportunities to collaborate through role division in home groups and expert groups. Based on these findings, the Jigsaw type Cooperative Learning model can be considered effective in improving the activeness of Grade V students at SDN Keleyan 2.